Pendekatan metode Quality Function Deployment sebagai usulan peningkatan kualitas produk keramik dinding - Gina Ramayanti; Ahmad Nalhadi; Rio Pujianto (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
PT. Arwana Nuansa Keramik is one of local tile manufacturer that produce both floor and wall tile products. Based on selling and customer complaint data in 2017 until 2018, there a lot of complaint for wall tile products and didn’t past the selling target each year. So, the aim of this study is to identified customer needs and wants in order to improve the quality of wall tile product PT. Arwana Nuansa Keramik that suit to customer needs with the result that the product can be compete with other competitor. This study using quality function deployment method until quality procedure phase. Quality Function Deployment is a method that concern in increasing the quality of a certain product based on customer needs and wants (Voice of Customer). By customer point of view, a quality is something that must have by the product, for wall tile in particular therefore it used for long life time. Identification of customer needs be obtained by distribute a questionneire to 50 respondents that recognized as a distributor of wall tile PT. Arwana Nuansa Keramik from Gorda until Tambak Area. Result of this study is a matrix that known as House of Quality matrix and contain several characteristics that can be used by PT. Arwana to improve the quality of their wall tile product. The Characteristics that shown by the matrix are strong products, ceramic products that have high quality and use advanced technology.